Comparação de modelos matemáticos para simulação de vibrações em rotores com defeitos estruturais - Dias, João Oscar Cervo (2023)
Rotors are essential components in various rotating machinery, such as electric motors and hydraulic turbines. Evaluating their dynamic behavior is crucial to ensure the integrity and safety of the equipment by controlling their oscillation amplitudes. Vibration analysis is a widely used method for detecting faults in mechanical equipment, with imbalance and misalignment being the main causes of vibration in rotating systems. Continuous monitoring and prognostics of rotor failures rely on sensors that capture vibration frequencies and algorithms capable of identifying frequency ranges associated with faults. However, creating databases solely based on real machines can be costly and time-consuming. An alternative approach is to employ numerical models capable of representing real machine data. The use of numerical solutions offers advantages such as reduced costs, rapid testing of different configurations, and the ability to simulate various types of equipment. This study aims to select and compare two distinct mathematical models for simulating vibrations in real rotors. The selected models have four degrees of freedom each and were numerically implemented using the Python programming language to simulate the WEG W22 IE3 electric motor rotor, with data provided by the company. Damage ranges were established according to applicable standards and subsequently combined into five damage states. The system responses were analyzed in the time and frequency domains.